Analisis Perbandingan Situs-Situs Pemerintahan di Indonesia dan Amerika Serikat - , Indra Fevbriana ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Website is a tool to facilitate the exchange and up-to-date information to internet users. A Website could be the work of individuals or indicate ownership of an organization, and usually the website shows some specific topics or special interests, in this case is government websites. The most important part of a website is the structure, content, and how to deliver information. This research discusses the comparative analysis between the Indonesian and the United States government websites by using 7Cs Framework. Each website will be assessed and compared whether eligible to 7Cs Framework.